Association of ABO and RH Blood Groups with Gestational Diabetes Mellitus in Patients Attending a Tertiary Care Hospital of Lahore, Pakistan - Shaheen, Sajida; Abdul Naeem, Muhammad; Farooq , Muhammad; Tariq Khan, Muhammad; Ashraf, Viqar; Arif, Amena (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find out any association of ABO and Rh blood groups with gestational diabetes mellitus (GDM). Study Design: Comparative cross-sectional study. Place and Duration of Study: Pathology and Gynecology departments of Combined Military Hospital-Lahore from Jun to Sep 2020. Methodology: A total of 250 patients of GDM and 250 pregnant ladies with normal glucose tolerance (NGT) were included in the study. The Oral glucose tolerance test (OGTT) was performed with a 75g glucose load, and results were interpreted according to the American Diabetes Association 2020 criteria. Blood glucose samples were taken in sodium fluoride containers in fasting conditions, 1 hour and 2 hours post-glucose load. Samples for blood groups were obtained in plain and EDTA containers. Blood glucose samples were analyzed using the Hexokinase method’s automated chemistry analyzer, Cobas c-501. ABO and RhD blood grouping were carried out by forward and reverse techniques in the blood bank of CMH Lahore. Results: A total of 250 (50%) pregnant ladies with OGTT suggestive of Gestational Diabetes Mellitus and 250 (50%) pregnant ladies with OGTT suggestive of Normal Glucose Tolerance (NGT) were included in the study. No statistically significant difference was observed with ABO and RhD blood groups among them (p=0.944). Conclusion: There is no significant association found between ABO and RhD blood groups with Gestational Diabetes Mellitus.